2020
DOI: 10.1002/art.41232
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of Remission in Two Early Rheumatoid Arthritis Cohorts Implementing Different Treat‐to‐Target Strategies

Abstract: ObjectiveThe objective of this study was to compare achievement of remission in 2 early rheumatoid arthritis (RA) treat‐to‐target (TTT) cohorts, a tight control cohort with a target of stringent remission in a randomized controlled trial and an observational cohort targeting a looser definition of remission in clinical practice.MethodsWe analyzed data from the Aiming for Remission in Rheumatoid Arthritis: a randomised trial examining the benefit of ultrasound in a Clinical Tight Control regimen (ARCTIC) trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
7
0
2
Order By: Relevance
“…It has good discriminative value, improving the classification criteria's sensitivity. In established RA, although it has been shown to be a good predictor in treatment response, remission assessment, and flare prediction, two trials comparing conventional T2T approach with US lead approach did not show significant differences in DAS28 remission, and lead to an increased treatment regimen is the US groups (60,61). Nevertheless, secondary analysis showed that Boolean remission was more often reached in the US arm (61).…”
Section: Discussionmentioning
confidence: 95%
“…It has good discriminative value, improving the classification criteria's sensitivity. In established RA, although it has been shown to be a good predictor in treatment response, remission assessment, and flare prediction, two trials comparing conventional T2T approach with US lead approach did not show significant differences in DAS28 remission, and lead to an increased treatment regimen is the US groups (60,61). Nevertheless, secondary analysis showed that Boolean remission was more often reached in the US arm (61).…”
Section: Discussionmentioning
confidence: 95%
“…Data for the present methodological investigation were provided by two Norwegian multicenter studies: the ARCTIC trial [12] and the NOR-VEAC prospective observational study [11,13]. Both enrolled patients with recently diagnosed rheumatoid arthritis (RA) and implemented treat-to-target strategies of different stringency as patients started disease-modifying anti-rheumatic drug (DMARD) therapy.…”
Section: Clinical Setting and Data Sourcesmentioning
confidence: 99%
“…The present methodological investigation was motivated by challenges arising in a previous study in which we used data from a prospective observational study as an external contemporaneous control group to be compared with a clinical trial [11]. The objectives of this paper are to 1) describe differences in missing data patterns during follow-up in a clinical trial versus an observational study and 2) empirically examine the impact of different missing data methods on study conclusions when using observational study data to form an external control group for a clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…Insofern wurde entschieden, dass zwar das primäre Ziel die komplette Remission ist, jedoch davon auszugehen ist, dass diese Qualität nicht bei allen RA-Patient*innen zu erreichen ist. In der internationalen Literatur wird dieses durchaus bekannte Problem meist so gelöst, dass von einer möglichen Akzeptanz niedriger Krankheitsaktivität gesprochen wird [ 35 , 36 ].…”
Section: Ergebnisseunclassified
“…Das wichtige Therapieziel Remission wird aus verschiedenen Gründen relativ häufig nicht erreicht ([ 36 , 40 , 41 ], s. auch QS 2). Das Hauptaugenmerk in der Diskussion bei diesem QS lag in der möglicherweise fehlenden, aber zum Teil durchaus notwendigen Ursachenforschung für die nicht erreichte Remission durch den*die Rheumatolog*in.…”
Section: Ergebnisseunclassified